Tanggung Jawab Notaris Atas Keterangan Hak Waris Yang Tidak Memasukan Seluruh Ahli Waris Berdasarkan KUHPerdata - Annisa Safira; Cindy Claudia Rondonuwu; Farah Millenia Elprianty (Jurnal Hukum Lex Generalis, 2025)
A notary is an official authorized to create authentic deeds with perfect evidentiary power, including in inheritance matters. Negligence in omitting certain heirs from an inheritance certificate may harm other heirs and result in legal accountability. Under the Civil Code, the notary may be subject to civil sanctions, such as compensation, if proven to have caused losses through unlawful acts. The inheritance certificate can be null and void if there is intent from the appearing party to misrepresent facts or documents. Alternatively, it may be annulled by a court decision based on a complaint from a harmed party.